WHO 2010 guidelines for prevention of mother-to-child HIV transmission in Zimbabwe: modeling clinical outcomes in infants and mothers. - Ciaranello, Andrea L; Perez, Freddy; Maruva, Matthews; Chu, Jennifer; Engelsmann, Barbara; Keatinge, Jo; Walensky, Rochelle P; Mushavi, Angela; Mugwagwa, Rumbidzai; Dabis, Francois; Freedberg, Kenneth A (PloS one, 2011)
The Zimbabwean national prevention of mother-to-child HIV transmission (PMTCT) program provided primarily single-dose nevirapine (sdNVP) from 2002-2009 and is currently replacing sdNVP with more effective antiretroviral (ARV) regimens.
Keywords: Anti-HIV Agents; Breast Feeding; Child; Female; HIV Infections; Humans; Infant, Newborn; Infectious Disease Transmission, Vertical; National Health Programs; Nevirapine; Outcome Assessment (Health Care); Practice Guidelines as Topic; Pregnancy; Pregnancy Complications, Infectious; Survival Analysis; World Health Organization; Young Adult; Zidovudine; Zimbabwe